1982
DOI: 10.1073/pnas.79.5.1634
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus DNA in cutaneous primary and metastasized squamous cell carcinomas from patients with epidermodysplasia verruciformis.

Abstract: DNA extracted from squamous cell carcinomas from patients with the chronic wart disease syndrome, epidermodysplasia verruciformis, was analyzed for the presence of human papillomavirus (HPV)-specific DNA sequences by Southern blot hybridization analysis. Employing an HPV probe obtained by molecular cloning of viral DNA purified from benign warts from these patients, we have unequivocally identified HPV-specific nucleotide sequences in squamous cell carcinomas from these patients. Restriction endonuclease mappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
87
0
6

Year Published

1983
1983
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(98 citation statements)
references
References 20 publications
5
87
0
6
Order By: Relevance
“…Ostrow et al reported the presence of HPV Type 5 in both a primary CSCC and its metastasis in 2 epidermodysplasia-verruciformis patients. 21 Nindl et al reported the presence of cutaneous HPV DNA in a primary CSCC and its metastasis in an immunocompetent and immunocompromised patient. 20 In our study however, we could not detect any persistent HPV infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ostrow et al reported the presence of HPV Type 5 in both a primary CSCC and its metastasis in 2 epidermodysplasia-verruciformis patients. 21 Nindl et al reported the presence of cutaneous HPV DNA in a primary CSCC and its metastasis in an immunocompetent and immunocompromised patient. 20 In our study however, we could not detect any persistent HPV infection.…”
Section: Discussionmentioning
confidence: 99%
“…The PM-PCR RHA method has previously been described in detail. 24,26 The method was designed for the identification of 25 established beta-PV types, namely genotypes 5,8,9,12,14,15,17,19,20,21,22,23,24,25,36,37,38,47,49,75,76,80,92,93 and 96.…”
Section: Dna Isolation and Pcr Reactions For Mutation Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cases positive for HPV by this intial screen were further analysed by Southern hybridisation using the restriction enzyme PstI. Filters containing 50 pg of purified HPV plasmid DNA of types 1, 2, 3, 4, 5, 8, 10, 12, 13, 14, 17, 19 and 20 (Heilman et al, 1980;Ostrow et al, 1982Ostrow et al, , 1983Kremsdorf et al, 1983Kremsdorf et al, , 1984Pfister et al, 1983a, b;Gassenmaier et al, 1984) mixed with 10 gAg of genomic DNA were also made for use in initial optimisation experiments. The sensitivity of this technique was investigated by performing Southern hybridisation analyses on serially diluted HPV 16 plasmid DNA mixed with a known concentration of genomic DNA.…”
Section: Histopathologymentioning
confidence: 99%
“…The HPV DNAs isolated from flat warts or macular lesions of EV patients have been analysed using restriction endonucleases, and several types of HPV, including 3, 5, 8, and 9, have been found in EV lesions (Orth et al, 1978;Pfister et al, 1981;Green et al, 1982;Kremsdorf et al, 1982). HPV-5 DNA has been reported to exist in carcinoma cells as unintegrated, free viral DNA (Orth et al, 1980;Ostrow et al, 1982). Although HPV is strongly suspected of being involved in carcinogenesis, little is known about this virus in comparison with other papovaviruses such as polyoma virus and SV40.…”
mentioning
confidence: 99%